Studi Perbandingan Kewenangan Kejaksaan Republik Indonesia Dengan Kejaksaan Malaysia Dalam Penanganan Perkara Tindak Pidana Korupsi - Nada Ulya Qinvi; alfitra alfitra (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
This study aims to explain the role of the Indonesian Public Prosecutor's Office and the Malaysian Prosecutor's Office in corruption crimes as well as the similarities and differences between the authorities of the Republic of Indonesia Prosecutors and the Malaysian Prosecutors in handling corruption cases. This research uses qualitative research research. In this research, the data collection method is carried out by using the library research technique, namely by studying the literature, legislation, books, official documents, and the writings of scholars related to this thesis. and analyzed using descriptive-qualitative methods. The approach used in this research is a statutory approach and a conceptual approach. The results of this study indicate that what becomes the similarity between the authority of the Republic of Indonesia Prosecutor's Office with the Malaysian Attorney is the role of the permanent prosecutor as public prosecutor, while what distinguishes the authority of the Republic of Indonesia Prosecutor's Office with the Malaysian Attorney is the authority in the field of prosecution.Keywords: Comparison, Authority, Attorney, Corruption Crime